The Urgency of Environmental Criminal Law Reform in Ensnaring Corporations: A Case Study of Tin Ecological Crimes by Harvey Moeis - Judijanto, Loso; Nurbeti, Nurbeti; Annisa, Febrina; Gustaliza, Resma Bintani (PT. Anagata Sembagi Education, 2025)
This study examines the urgency of environmental criminal law reform in Indonesia in ensnaring corporations as the main perpetrators of ecological crimes, especially through a case study of tin mining involving Harvey Moeis. Although Law Number 32 of 2009 concerning Environmental Protection and Management (PPLH Law) regulates the criminalization of business entities, its implementation is still limited to an individualistic approach that is difficult to reach corporate accountability structurally. The inconsistency of the PPLH Law with Law Number 40 of 2007 concerning Limited Liability Companies (PT Law) weakens the effectiveness of law enforcement, because the provisions of social and environmental responsibility in the PT Law are administrative without adequate criminal threats. The dominant vicarious liability approach still fails to accommodate the principles of strict liability and corporate mens rea, so corporations often escape serious criminal sanctions. The research uses a normative qualitative approach with the analysis of primary and secondary legal materials to understand legal constraints and prepare reform recommendations. The results affirm the need for harmonization across laws, strengthening corporate collective accountability, and applying progressive principles in penalties. These reforms are essential to realize effective ecological justice and corporate accountability for environmental crimes in a systemic and sustainable manner.